Effect of anise seed (Pimpinella anisum L.) and protease alone or in combination on growth performance, carcase characteristics, humoral immunity, nutrients digestibility and cecal microbiota in Japanese quails - Asad Sultan; Sidra Bibi; Shabana Naz; Ziaul Islam; Abdulwahed Fahad Alrefaei; Rifat Ullah Khan; Samia H. Abdelrahman; Maria Selvaggi (Food and Agricultural Immunology)
The trial investigated the effects of anise seed powder and protease, alone and combined, in Japanese quail diets. 540 seven-day-old quails were divided into four groups: Control (basal diet), Anise Seed Group (1000 mg/kg anise seed powder), Protease Enzyme Group (30,000 IU/kg Bacillus subtilis-derived protease enzyme), and a combination of anise powder and protease. The combination significantly increased weight gain and dressing percentage compared to the control. Quails receiving protease, anise powder, or both showed higher antibody titers against infectious diseases. The population of beneficial Lactobacillus increased in groups receiving protease and the combination. Additionally, the presence of harmful bacteria like Escherichia coli and Salmonella decreased significantly in quails supplemented with both protease enzyme and anise powder. In summary, combining protease and anise powder improved growth performance, immune responses, increased Lactobacillus population, and decreased pathogenic bacteria in quails.